2009
DOI: 10.3922/j.psns.2009.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent ethanol binge exposure impairs object recognition but spares contextual and tone fear memory in adolescent rats.

Abstract: Adolescent brain development seems to be important for the maturation of brain structures and behavior. Intermittent binge ethanol drinking is common among adolescents, and this type of drinking can induce brain damage and cognitive deficits. In addition, emotional changes are frequently seen in alcoholics and rodents treated with ethanol. Considering the close relation between emotional arousal and cognitive responses, the present work investigates if intermittent ethanol binge exposure could differentially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…In agreement with earlier reports, we observed that our EtOH treatment during adolescence induced both short- (i.e., when measured 5 days after its administration; Study 2) and long-term (i.e., when measured 37 days after its administration; Study 1) memory impairments in the OR task (Figs 3 and 4B respectively) [ 6 , 42 , 55 57 ]. In addition, in Study 3 we found the same long-lasting effects when EtOH was given during adulthood ( Fig 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with earlier reports, we observed that our EtOH treatment during adolescence induced both short- (i.e., when measured 5 days after its administration; Study 2) and long-term (i.e., when measured 37 days after its administration; Study 1) memory impairments in the OR task (Figs 3 and 4B respectively) [ 6 , 42 , 55 57 ]. In addition, in Study 3 we found the same long-lasting effects when EtOH was given during adulthood ( Fig 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…Impairment of object discrimination had already been shown for short interval in adolescent rats exposed to a CIA (ISI: 1 minute, 3 g/kg, i.p., for 2 consecutive days at 48‐hour intervals over 14 days; Pascual et al., ) or longer interval in adolescent mice (ISI: 1 hour; 2.5, 2.5, and 2 g/kg; i.p., at 2‐hour intervals every 5 days over 15 days; Lacaille et al., ), or rats (ISI: 24 hours; 2.5 or 5 g/kg at 48‐hour intervals over PND 30 to 60; Schaaffhausen et al., ), suggesting deleterious effects of alcohol exposure in adolescence on object recognition performances with both short and long ISI. Discrimination deficits after a shorter retention delay (1 minute) often suggest impairment of encoding.…”
Section: Discussionmentioning
confidence: 99%